1966
DOI: 10.1128/jb.91.1.134-142.1966
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Thermal Injury of Staphylococcus aureus

Abstract: posure of Staphylococcus aureus MF 31 to sublethal temperatures produced a temporary change in the salt tolerance and growth of the organism. After sublethal heat treatment at 55 C for 15 min, more than 99% of the viable population was unable to reproduce on media containing 7.5% NaCl. The data presented demonstrate that thermal injury, in part, occurred owing to changes in the cell membrane, which allowed soluble cellular components to leak into the heating menstruum. When the cells were placed in a limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
2
1

Year Published

1970
1970
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(130 citation statements)
references
References 23 publications
(17 reference statements)
9
117
2
1
Order By: Relevance
“…A thermal treatment of 55 ∘ C for 15 min has been reported to negatively affect the growth of S. aureus. 42 Similar conditions were shown during the cooking of Cocido cheese (50 and 60 ∘ C for 20 min). Nevertheless, despite this reduction, we found that the final S. aureus count in dairies D1, D2, D5 and D6 surpassed the Mexican permissible limit (3 log 10 colony-forming units (CFU) mL −1 ).…”
Section: Microbiological Qualitysupporting
confidence: 53%
“…A thermal treatment of 55 ∘ C for 15 min has been reported to negatively affect the growth of S. aureus. 42 Similar conditions were shown during the cooking of Cocido cheese (50 and 60 ∘ C for 20 min). Nevertheless, despite this reduction, we found that the final S. aureus count in dairies D1, D2, D5 and D6 surpassed the Mexican permissible limit (3 log 10 colony-forming units (CFU) mL −1 ).…”
Section: Microbiological Qualitysupporting
confidence: 53%
“…Apparently, the lack of available nutrients prevented recovery. Such an occurrence has been shown with heat-injured bacteria also deprived of nutrients (Iandolo and Ordal, 1966).…”
Section: Resultsmentioning
confidence: 77%
“…Such a degradation may be responsible for thermally-induced death in this strain (1,3) and in other strains of Staph. aweus (6,7). It is, however, difficult to link this degradation with loss of viability of Staph.…”
Section: Resultsmentioning
confidence: 99%